A quasi-periodic modulation of the iron line centroid energy in the black hole binary H1743−322. Issue 2 (25th May 2016) - Ingram, Adam; van der Klis, Michiel; Middleton, Matthew; Done, Chris; Altamirano, Diego; Heil, Lucy; Uttley, Phil; Axelsson, Magnus
Abstract: Accreting stellar-mass black holes often show a 'Type-C' quasi-periodic oscillation (QPO) in their X-ray flux and an iron emission line in their X-ray spectrum. The iron line is generated through continuum photons reflecting off the accretion disc, and its shape is distorted by relativistic motion of the orbiting plasma and the gravitational pull of the black hole. The physical origin of the QPO has long been debated, but is often attributed to Lense–Thirring precession, a General Relativistic effect causing the inner flow to precess as the spinning black hole twists up the surrounding space–time. This predicts a characteristic rocking of the iron line between red- and blueshift as the receding and approaching sides of the disc are respectively illuminated. Here we report on XMM–Newton and NuSTAR observations of the black hole binary H1743−322 in which the line energy varies systematically over the ∼4 s QPO cycle (3.70σ significance), as predicted. This provides strong evidence that the QPO is produced by Lense–Thirring precession, constituting the first detection of this effect in the strong gravitation regime. There are however elements of our results harder to explain, with one section of data behaving differently than all the others. Our result enables the future application of tomographic techniques to map the inner regions of black hole accretion discs.